OTHER BOOKS RECEIVED. (Catholic Historical Review, 2013)
A bibliography of several books received by the journal is presented, including "The Catholic Church: What Everyone Needs to Know," by John L. Allen, Jr., "Genius Born of Anguish: The Life & Legacy of Henri Nouwen," by Michael W. Higgins and Kevin Burns, and "Dante and the Blessed Virgin," by Ralph McInerny.